Rhodium-catalyzed C–H activation of hydrazines leads to isoquinolones with tunable aggregation-induced emission properties1. Issue 76 (10th October 2015) - Yu, Bole; Chen, Ying; Hong, Mei; Duan, Pingping; Gan, Shifeng; Chao, Hui; Zhao, Zujin; Zhao, Jing
<x xml:space="preserve">Abstract</x> We report a RhIII-catalyzed synthesis of isoquinolones via C–H activation/annulation of benzoylhydrazines and alkynes for AIE studies.